The Dynamics of Islamic Education in Indonesia: : Negotiating Tradition, Modernity, and Socio-Political Transformations (1900–2000) - Arthapurna Vidhiputra, Rumi (Jurnal Ceteris Paribus, 2025)
The historical evolution of Islamic education in Indonesia from 1900 to 2000 illustrates a dynamic interplay between tradition and modernity, profoundly influenced by socio-political transformations. Throughout the 20th century, Islamic educational institutions, particularly madrasahs and pesantren, adapted to contemporary educational demands while steadfastly maintaining their religious foundations. This process reflects not merely a reaction to external pressures but a deliberate endeavour by local scholars and educators to synthesize classical Islamic teachings with modern pedagogical advancements. The integration of secular subjects, the standardization of curricula, and the adoption of innovative teaching methodologies exemplify a dialectical transformation. This transformation is a delicate balance, wherein traditional Islamic education engaged with modern reforms without completely relinquishing its heritage. This evolution challenges the conventional narrative of educational modernization as a linear progression toward Western paradigms, instead highlighting the agency of Indonesian Islamic institutions in crafting their educational trajectories. This nuanced perspective underscores the complexities inherent in the development of Islamic education in Indonesia, revealing how these institutions responded to changing societal demands and actively shaped their identities and practices in a constantly evolving socio-political landscape.